1984
DOI: 10.1007/bf00273911
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and glucagon in spontaneously diabetic non-obese mice

Abstract: To investigate the role of glucagon in the development of diabetes mellitus, spontaneously diabetic non-obese mice were studied before (group 1) and after the onset of diabetes mellitus (group 2). In group 1, fasting blood glucose and insulin in plasma and pancreas did not differ significantly, while plasma glucagon was elevated (48.9 +/- 10.4 versus control 18.6 +/- 6.0 pmol/l). In group 2, the insulin content of plasma and the pancreas were markedly reduced, whereas plasma glucagon was elevated (180.9 +/- 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
(33 reference statements)
1
14
1
Order By: Relevance
“…In this study, supplementation of genistein and daidzein lowered the blood glucose level and plasma urea nitrogen concentration simultaneously, while elevating plasma insulin and C-peptide levels. Plasma glucagon has been shown to be elevated in the NOD mice prior to absolute insulin deficiency [44]; however, in the current study supplementation of genistein and daidzein did not affect the plasma glucagon level. Ali et al [45] reported that 0.1% soy isoflavones mixture lowered the plasma glucagon level in lean rats, but isoflavones did not alter the plasma glucagon concentration in genetic model of obesity and diabetes.…”
Section: Hepatic Malic Enzyme G6pd Fatty Acid β-Oxidation and Cpt contrasting
confidence: 48%
“…In this study, supplementation of genistein and daidzein lowered the blood glucose level and plasma urea nitrogen concentration simultaneously, while elevating plasma insulin and C-peptide levels. Plasma glucagon has been shown to be elevated in the NOD mice prior to absolute insulin deficiency [44]; however, in the current study supplementation of genistein and daidzein did not affect the plasma glucagon level. Ali et al [45] reported that 0.1% soy isoflavones mixture lowered the plasma glucagon level in lean rats, but isoflavones did not alter the plasma glucagon concentration in genetic model of obesity and diabetes.…”
Section: Hepatic Malic Enzyme G6pd Fatty Acid β-Oxidation and Cpt contrasting
confidence: 48%
“…The neoformation of alpha cells was recently described in a study of the non-obese diabetic (NOD) mouse (O'Reilly et al 1997), an experimental model of type 1 autoimmune diabetes known to display hyperglucagonemia similar to that found in human type 1 diabetes (Ohneda et al 1984). The alpha cells were thought to be derived both from progenitor cells present in ductal areas and from replication of islet alpha cells.…”
Section: Introductionmentioning
confidence: 85%
“…It is noteworthy that the low level of insulin in NOD mice is correlated with increase secretion of glucagon in treatead and non-treated with insulin individuals. Thus, is concluded that insulin deficiency and glucagon hypersecretion might have an important role in the development and clinical progress of diabetes in NOD mice [32]. Pinealectomy in newborn mice is followed by a more rapid onset of diabetes in female and supplementary melatonin administration protects the animals.…”
Section: Spontaneous Iddm Based On Animal Modelsmentioning
confidence: 99%